ANALYSIS OF THE ECOLOGICAL STATE OF WATER IN THE SALAR CANAL PASSING THROUGH THE TASHKENT REGION (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
This article is devoted to the analysis of the ecological state of the water of the Salar channel, one of the main sources of water in the Tashkent region, the identification of pollution sources, the assessment of hydrochemical indicators and their impact on the ecosystem, as well as the description of the growing level of water pollution with heavy metals.